Risk Factors, Clinical Profile and Association of Clinical Grading With Radiological Grading of Adenoid Hypertrophy in Children - Akhtar, Gulshan; Khanam, Afroza; Rahman, Mohammad Abdur; Islam, Quazi Rakibul; Chowdhury, Nurun Nahar (Journal of Shaheed Suhrawardy Medical College, 2024)
BACKGROUND: Adenoid hypertrophy producing obstructive airway symptoms is the most commonly encountered pediatric ENT problem. Clinical symptoms in combination with lateral nasopharyngeal x ray is a reliable technique for selection of children requiring surgical intervention. METHODOLOGY: The current cross sectional prospective study was conducted among 250 children aged 3-12 years with clinical symptoms and radiological evidence suggestive of enlarged adenoids, at Pediatric outpatient department of a tertiary care center, Dhaka, during 1-year period. RESULT: In our current study, majority children (74%) with adenoid hypertrophy were 3-6 years old followed by 26% between 7-12 years. 66% children were male and 34% were female with a male to female ratio of 1.9:1. 44% children were from lower class family and history of atopy was present among 54% children. Clinical grading of adenoid hypertrophy was done on the basis of presenting symptoms (mouth breathing, snoring, sleep disturbances and adenoid facies) and radiological grading was done from calculating adenoid nasopharyngeal ratio. Correlation between clinical scoring and radiological grading of adenoid hypertrophy among study population was observed. Clinical score of 0-4, 5-8, 9-12 and 13-16 was graded clinically into Grade I, II, III and IV respectively. Highly significant p value (.000) was observed in Grade II clinical and radiological grade of enlarged adenoid. The remaining clinical and radiological grade of enlarged adenoids showed significant p value .031, .024 and .019 among grade I, III and IV respectively. CONCLUSION: Though various diagnostic modalities for detection of degree of obstruction caused by enlarged adenoids are available, clinical scoring in combination with radiological grading can be effectively used to select patients requiring surgical intervention for pediatric adenoid hypertrophy. J Shaheed Suhrawardy Med Coll 2022; 14(2): 11-17